Recycling Apparent Waste Into Biologicals: The Case of Umbilical Cord Blood in Italy and Spain - Rebulla, Paolo; Querol, Sergio; Pupella, Simonetta; Prati, Daniele; Delgadillo, Joaquin; De Angelis, Vincenzo (Frontiers in Cell and Developmental Biology, 2022)
Most public cord blood banking programs are currently facing financial difficulties due to a progressive decline in the number of cord blood transplants performed worldwide and to a high discard rate of the donated units caused by progressively increasing thresholds of the stem cell dose required to perform safe and effective hemopoietic cord blood transplants. Recycling a proportion of unused cord blood units to prepare novel cord blood components obtained with minimal manipulation (platelets, plasma, red blood cells) and to develop more technologically complex products regulated in the US as Cellular and Gene Therapy Products and in Europe as Advanced Therapy Medicinal Products (e.g. virus-specific T cells [VST], natural killer [NK] cells, induced pluripotent stem cells [iPSCs]) is a promising strategy to increase the therapeutic value and reduce the financial deficits of public cord blood banking. Based on encouraging preliminary evidences reported in the literature, additional laboratory studies, large multicenter clinical trials and international regulatory harmonization are necessary to achieve these important goals. This article describes organizational, methodological and regulatory advancements developed in Italy and Spain to promote the clinical use of cord blood platelets, plasma and red blood cells.